Uma análise da abordagem sobre argumentações e provas numa coleção do ensino médio - Mendes, Lourival Junior (2007)
The purpose of this study was to investigate the role of proofs and demonstration on textbooks of high school. This work contributes with APROVA ME, a project that aims to investigate, analyze and propose activities for the learning of proofs and demonstration in school mathematics. The text books from Manoel Paiva was analyzed; three volumes constituted his collection and it was approved by the National Program that evaluate high school text books. It was distributed among public schools in the state of Sao Paulo, including the one I teach. Since text books are, in general, the solely source for classroom teachers, and many studies point out the impact of text books on teacher s way of teaching and consequently impact on students learning, to investigate how it deals with proofs and demonstration may help to show new ways of teaching proofs in schools. Our investigation focused on the topics: Number sets; functions; arithmetic and geometric progressions; parallelism and perpendiculars. After analyzing the three volumes, based on Balacheff, Villiers and IREM group, it was possible to classify the proofs that were privileged by the author. I discuss and present suggestions to enhance the teaching of proofs related to the analyzed topics